Komite Audit Dan Kepemilikan Saham Institusional Sebagai Pendorong Pengungkapan Corporate Social Responsibility (CSR) Pada Perusahaan Basic Material Yang Terdaftar Di Bursa Efek Indonesia (2022-2024) - Gina Panjaitan; Jhon Rinendy; Lorina Siregar Sudjiman (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2026)
This study aims to examine the effect of the audit committee and institutional share ownership on Corporate Social Responsibility (CSR) disclosure in Basic Material sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The study applies a quantitative approach using secondary data obtained from companies’ annual reports. The sample was determined using purposive sampling, resulting in a total sample of 30 companies. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS software version 22. The results show that partially, the audit committee does not have a significant effect on CSR disclosure. In contrast, institutional share ownership has a positive and significant effect on CSR disclosure. Simultaneously, both independent variables significantly affect CSR disclosure. The coefficient of determination indicates that both variables are able to explain 17.4% of the variation in CSR disclosure. The findings suggest that institutional investors play an important role in encouraging increased transparency in CSR disclosure in Basic Material sector companies.